2016
DOI: 10.1097/md.0000000000003398
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Agreement of High-Resolution Magic Angle Spinning Magnetic Resonance Spectroscopic Profiles in the Metabolic Characterization of Breast Cancer

Abstract: High-resolution magic angle spinning (HR-MAS) magnetic resonance (MR) spectroscopy data may serve as a biomarker for breast cancer, with only a small volume of tissue sample required for assessment. However, previous studies utilized only a single tissue sample from each patient. The aim of this study was to investigate whether intratumoral location and biospecimen type affected the metabolic characterization of breast cancer assessed by HR-MAS MR spectroscopyThis prospective study was approved by the institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 27 publications
(28 reference statements)
3
22
1
Order By: Relevance
“…Interestingly, all cores but one were correctly classified (Figure A), suggesting that cores sampled from the same tumor were, in general, more similar than cores sampled from two different tumors, despite the observed intratumoral variability. This is in agreement with the conclusion of Park et al, where the authors compared metabolite levels in the center of the tumor with those observed at the tumor periphery in surgically resected breast cancer tissue. Overall, the authors concluded that the intratumoral location had a limited influence on the observed metabolite levels .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Interestingly, all cores but one were correctly classified (Figure A), suggesting that cores sampled from the same tumor were, in general, more similar than cores sampled from two different tumors, despite the observed intratumoral variability. This is in agreement with the conclusion of Park et al, where the authors compared metabolite levels in the center of the tumor with those observed at the tumor periphery in surgically resected breast cancer tissue. Overall, the authors concluded that the intratumoral location had a limited influence on the observed metabolite levels .…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with the conclusion of Park et al, where the authors compared metabolite levels in the center of the tumor with those observed at the tumor periphery in surgically resected breast cancer tissue. Overall, the authors concluded that the intratumoral location had a limited influence on the observed metabolite levels . The results of the present investigation also agree with the findings mentioned by Cao et al, who sampled multiple biopsies and suggested that the interpatient variation was higher than the intrapatient variation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Studies of breast cancer (BrCa) have shown HRMAS MRS to be a promising tool in cancer diagnosis, treatment monitoring, and prediction of prognosis. [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] Here, we will focus our review on four interesting aspects: metabolic differences between malignant and non-malignant breast tissues, correlations between metabolites and pathologic features of BrCa, predictions of the response to the clinical treatment and the prognosis of BrCa with metabolic information, and the relationships of metabolite, gene, and protein information.…”
Section: Breast Cancermentioning
confidence: 99%